Estratégia para armazenamento e recuperação de experiência multimídia em telemedicina: um estudo de caso no Projeto Ambiente de Vídeo Colaboração em Saúde (GTAVCS) . - Braga Junior, Wolgrand Cardoso (2013)
Applications with multimedia content are becoming more popular, especially interactive and real-time applications. Among these applications stands multimedia systems for telemedicine that allows users to share information as surgical medical videos and patient data. This paper presents an approach to capture, represent and retrieve multimedia experiences in telemedicine. Therefore, a strategy that describes ways to store data, a notation for describing the multimedia experience and features that allow the retrieval and display of the experiences recorded was drafted. Furthermore, a service based on this strategy was implemented in the context of the Environment Video Collaboration in Health project (GTAVCS) and the Arthron tool. The Arthron tool allows management and distribution of media streams in real time and its main application is telemedicine allowing the transmission of live surgeries. The user experience when streaming live surgery involves multiple streams, their alternations, additional flows (such as exams or medical imaging), featuring a complex multimedia experience. The strategy presented in this paper is applied to precisely reproduce that experience, enabling their retrieval and viewing on demand. To validate the strategy, tests were conducted using the recording and retrieval service implementation for Arthron constructed to compare the users' perception about the experience in real time and experience reproduced by the tool.